2019
DOI: 10.1155/2019/1418251
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Frequencies of Th17 and Tc17 Cells in Patients Infected with Avian Influenza A (H7N9) Virus

Abstract: The outbreak of avian influenza A (H7N9) virus infection, with a high mortality rate, has caused concern worldwide. Although interleukin-17- (IL-17-) secreting CD4+ T (Th17) and CD8+ T (Tc17) cells have been proven to play crucial roles in influenza virus infection, the changes and roles of Th17 and Tc17 cells in immune responses to H7N9 infection remain controversial. In this study, we found that the frequencies of Th17 and Tc17 cells among human peripheral blood mononuclear cells (PBMCs) as well as IL-17A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…The IL-17A signaling in airway cells was downregulated in H7N9-infected NHBE cells in IPA analysis, and IL-17 was negatively expressed in our cytokine analysis. The result is consistent with other studies: Bao et al [25] claimed that the IL-17A protein and mRNA levels were decreased in patients with H7N9 infection and a restored Th17 and Tc17 cell frequency might serve as a biomarker for disease progression in patients infected with this virus.…”
Section: Discussionsupporting
confidence: 93%
“…The IL-17A signaling in airway cells was downregulated in H7N9-infected NHBE cells in IPA analysis, and IL-17 was negatively expressed in our cytokine analysis. The result is consistent with other studies: Bao et al [25] claimed that the IL-17A protein and mRNA levels were decreased in patients with H7N9 infection and a restored Th17 and Tc17 cell frequency might serve as a biomarker for disease progression in patients infected with this virus.…”
Section: Discussionsupporting
confidence: 93%
“…A pilot study of patients with symptoms of respiratory tract infection demonstrated that the H3N2 influenza infection exhibited increased levels of Th17 cytokines concerned with pathogenesis and immune regulation (Antalis et al, 2019 ). In the patients infected with avian influenza A (H7N9) virus, the decreased Th17 and Tc17 cell levels are associated with disease severity however, the mechanism remains unknown (Bao et al, 2019 ). In PR8 H1N1 infected BALB/c mice the IL‐17A and IL‐17F mRNA levels were detected after 2 days postinfection.…”
Section: Role Of Il‐17 In Different Viral Infectionsmentioning
confidence: 99%
“…IL-17 is a remarkably pleiotropic cytokine that plays a specific role in host immune response. A wide range of immune cell populations, such as Th17 cells , neutrophils, natural killer (NK) cells, mast cells, natural killer T (NKT) cells, CD8+ T cells and group 3 innate lymphoid cells produce IL-17 [7][8][9][10]. IL-17 has a crucial role in the preservation of tissue integrity and initiation of protective immune responses to infectious microorganisms, mostly at epithelial barrier sites [11].…”
Section: Discussionmentioning
confidence: 99%